The correlation between vitamin D3 and IL-17 in rheumatoid arthritis patients - Alaa A. Saleh; Shereen Al-Ali (Genius Journals, 2022)
Rheumatoid. arthritis. (RA) is define as a chronic. inflammatory disorders that have autoimmune etiologies. It is characterized. by inflamed joints. A total of 55 individual included 36 adult Rheumatoid arthritis patients from both sexes, age 21-73 yrs and 19 healthy controls (HCS). All patients were visitors of Rheumatoid arthritis center located in Basra teaching hospital and fill a related questionnaire. The sera were tested for the existences of interlukines-17A (IL-17A) and Vitamin D (VD3) using ELISA kit. Pearson’s correlation was used to investigate various relationships. The results were statistically analyses using normality and Mann-Whiteny test in Minitab. IL-17A estimated level was higher in RA in compare to HC (121.33±71.7 and 96±57.97, respectively). In addition, the estimated level VD3 was lower in RA in compare to HCs (10.87±4.07 and 42.17±7.19, respectively). The correlation between the age of the study subjects and the level of IL17A showed that there is no correlation between the two parameters in RA. The relationship between the VD3 and the level of IL-17A was negative in RA patients.
Keywords: Rheumatoid arthritis; vitamin D3; interleukin; correlation